Performance evaluation of ESG theme fund: Evidence from China - Chen, Junkuang (2022)
The ESG philosophy has grown rapidly in China in recent years and has subsequently given rise to a number of financial instruments, including ESG funds. Although some low carbon and social responsibility funds already existed in the Chinese market in earlier years, the ESG concept had not yet received much attention in China. Since the introduction of the 'carbon peaking and carbon neutrality goals', a large number of ESG funds have appeared in the market. It is perfectly in line with the policy-oriented nature of the Chinese market, where the activities of financial markets are highly relevant to national policies. One of the characteristics of Chinese financial institutions and related financial products is to serve the national strategy. Currently, 60% of ESG-related funds in the Chinese market have been established within the last two years, and two-thirds of them are less than one year old. In this context, this study aims to address two questions. The first is how well ESG funds are performing in the Chinese market; the second is whether investments by ESG funds can in turn lead to improved ESG score of invested companies. In terms of economic performance, the empirical results from the Carhart four-factor model suggest that overall ESG funds have less systematic risk than market portfolio risk, while funds with higher ESG scores tend to have greater systematic risk. Regression results from the T-M, H-M and C-L models indicate that ESG funds have excellent stock selection but poor timing ability, and the average monthly return of ESG funds is higher than the market return by approximately 1%. With regard to investment style, ESG funds prefer to invest in companies with small market capitalization and long life span. Also, strong growth and excellent historical returns are considered by the ESG funds. As there is no ESG scoring standard for funds in the Chinese market, this study scores funds according to the ESG scores of their equity holdings. From the scoring results, the ESG scores of funds vary widely. As for the impact of fund holdings on corporate ESG score, longer fund holdings can contribute to the improvement of corporate ESG scores, but high ESG fund holdings are not conducive to the improvement of corporate ESG scores. As a representative of secondary market investment and financing tool, ESG fund does not have a strong driving effect on enterprises to improve their ESG scores. However, it is worth noting that the current ESG fund size in the Chinese market is still small. With the popularity of ESG investment concept, it is expected that the related funds and investment products will see explosive growth in the next few years. And we need to pay attention to whether such funds strictly follow ESG investment philosophy to select ESG-performing companies as investment targets and their further affect of the invested firms.